ANALYSIS OF EPISTEMIC BELIEFS OF PROSPECTIVE SCIENCE TEACHERS IN CARRYING OUT PRACTICUM ACTIVITIES REVIEWED FROM MOTIVATION - Tria Mariska; Aristiawan (Science Education, Institut Agama Islam Negeri Ponorogo, 2026)
Science education, especially in the field of Natural Sciences (IPA) plays an important role in shaping students' skills and understanding, especially through practicum activities as a means of applying theory in a real context. This study aims to analyze the influence of epistemic beliefs of prospective science teachers in practicum activities, identify the role of motivation on epistemic beliefs, and find out the relationship between the two. Based on the purpose of the study, this study was designed using a descriptive qualitative method with observation, interview, and questionnaire techniques on 30 prospective science teachers in the Tadris Science laboratory at IAIN Ponorogo. The use of questionnaires in this qualitative research serves as supporting data to strengthen the findings, with the main analysis still emphasizing qualitative descriptiveness. Then the data from the research results are compared with the existing research theory which will later provide research conclusions. The results of the study show that the majority of prospective science teachers have high epistemic beliefs, with a percentage of 80% in the high category. This belief includes four dimensions, namely, certainty of knowledge, simplicity, source of knowledge, and justification. In addition, 52% of respondents have the motivation to develop their potential through practicum activities. There is a positive relationship between epistemic beliefs and motivation, where strong beliefs can increase motivation to actively engage in practicums. This study concludes that the development of epistemic beliefs and good motivation is very important to improve the quality of science education in Indonesia.